METHODOLOGICAL FOUNDATIONS OF FOREIGN LANGUAGE INSTRUCTION FOR TRANSLATORS IN DISTANCE LEARNING ENVIRONMENTS - Tuxtasinov Ilhomjon Madaminovich (ARAB TILI GLOBALLASHUV DAVRIDA: INNOVATSION YONDASHUVLAR VA O‘QITISH METODIKASI MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2025)
The rapid expansion of distance learning has significantly reshaped translator education, particularly in the field of foreign language instruction. While online formats provide flexibility and access, they also require a reconsideration of traditional methodological principles used in training translators. This article examines the methodological foundations of foreign language instruction for translators in distance learning environments. Drawing on competence-based education, communicative language teaching, and digital pedagogy, the study identifies key methodological principles and instructional strategies that support the development of linguistic, pragmatic, and translation-related competences. The findings highlight the importance of task-based learning, interactive digital tools, and professional orientation in ensuring the effectiveness of foreign language instruction for future translators in online settings.